PROBLEMS OF ENVIRONMENTAL PREDICTION FOR SOLVING PROBLEMS SURFACE WATERS FROM DISCHARGES INTO WATER BODIES - , О. А. (Municipal economy of cities. Series: «Economy science», 2013)
Analyzes the methodological basis of forecasting the state of the water body for regulations of wastewater discharges on the example of the watercourse. It is shown that the problems of environmental forecasting are general in nature and are caused by the complexity of ecosystems. We give demos calculations.